Impact of study outcome on submission and acceptance metrics for peer reviewed medical journals: six year retrospective review of all completed GlaxoSmithKline human drug research studies. (21st April 2017) - Evoniuk, Gary; Mansi, Bernadette; DeCastro, Barbara; Sykes, Jennie
Abstract : Objectives  To determine whether the outcome of drug studies influenced submission and/or acceptance rates for publication in peer reviewed medical journals. Design  A six year retrospective review of publication status by study outcome for all human drug research studies conducted by a single industry sponsor (GlaxoSmithKline) that completed from 1 January 2009 to 30 June 2014 and were therefore due for manuscript submission (per the sponsor's policy) to peer reviewed journals within 18 months of study completion—that is, 31 December 2015. In addition, manuscripts from studies completing after 30 June 2014 were included irrespective of outcome if they were submitted before 31 December 2015. Setting  Studies conducted by a single industry sponsor (GlaxoSmithKline) Studies reviewed  1064 human drug research studies. Main outcome measures  All studies were assigned a publication status at 26 February 2016 including (as applicable): study completion date, date of first primary manuscript submission, number of submissions, journal decision(s), and publication date. All studies were also classified with assessors blinded to publication status as "positive" (perceived favorable outcome for the drug under study), "negative" (perceived unfavorable outcome for the drug under study), mixed, or non-comparative based on the presence and outcome of the primary outcome measure(s) for each study. "Negative" studies included safety studies in which the primary outcome was achieved but was adverse for the drug under study. For the total cohort and each of the four study outcomes, measures included descriptive statistics for study phase, time from study completion to submission and publication, and number and outcome (accepted/rejected) of publication submissions. Results  Of the 1064 studies (phase I-IV, interventional and non-interventional) included, 321 had study outcomes classified as positive, 155 as negative, 52 as mixed, and 536 as non-comparative. At the time of publication cut-off date (26 February 2016), 904 (85%) studies had been submitted for publication as full manuscripts and 751 (71%) had been successfully published or accepted, with 100 (9%) still under journal review. An additional 77 (7%) studies were conference abstracts and were not included in submission or publication rates. Submission rates by study outcome were 79% for the 321 studies with positive outcomes, 92% for the 155 with negative outcomes, 94% for the 52 with mixed outcomes, and 85% for the 536 non-comparative studies; while rates of publication at the cut-off date were 66%, 77%, 77%, and 71%, respectively. Median time from study completion to submission was 537 days (interquartile range 396-638 days) and 823 days (650-1063 days) from completion to publication, with similar times observed across study outcomes. First time acceptance rates were 56% for studies with positive outcomes and 48% for studies with negative outcomes. Over 10% of studies across all categories required three or more submissions to achieve successful publication. At the time of analysis, 83 studies had not been submitted for publication, including 49 bioequivalence studies with positive outcomes and 33 non-comparative studies. Most studies (98%, 1041/1064) had results posted to one or more public registers, including all studies subject to FDAAA (Food and Drug Administration Amendments Act) requirements for posting to www.clinicaltrials.gov . Conclusions  Over the period studied, there was no evidence of submission or publication bias: 92% of studies with negative outcomes were submitted for publication by the cut-off date versus 79% of those with positive outcomes. Publication rates were slightly higher for studies with a negative (that is, unfavorable) outcome compared with a positive outcome, despite a slightly lower rate of acceptance at first submission. Many studies required multiple submission attempts before they were accepted for publication. Analyses focusing solely on publication rates do not take into account unsuccessful efforts to publish. Sponsors and journal editors should share similar information to contribute to better understanding of issues and barriers to full transparency.